Stock Price Analysis of Infrastructure Sector Companies Listed on the Indonesia Stock Exchange - Eka Yulianti; Yul Tito Permadhy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This type of research is quantitative, with the aim of finding factors that have an influence on stock prices in infrastructure sector companies. By utilizing probability sampling techniques with slovin formula, 30 infrastructure companies listed on the Indonesia Stock Exchange were found for research samples. The hypothesis test used in this study was regression of panel data and using the E-views 12.0 program and the significance level of 5%. The results found as follows (1) there was influence of profitability on the stock prices of infrastructure sector companies, (2) there was no influence of solvency on the stock prices of infrastructure sector companies, (3) there was influence of inflation on the stock prices of infrastructure sector companies, and (4) there was influence of exchange rates on the stock prices of infrastructure sector companies.